A infância como direito: o currículo no processo da universalização da educação infantil - Zimermann, Adriana de Mores (2014)
The child education has an important social role on the social and human development. This paper has the aim to analyze how the curriculum references, which guide the child education, provide some help following the curricular proposal, according to the purpose of the child education universalization. So, they were analyzed the National Curricular Referential (RCNEI) and the documents referring to the educational policies for the Child Education, among them the Indicators of quality for the Child Education. The paper was structured into three parts: firstly, it was approached the historical, social, cultural, psychological and political aspects which influenced the child attending and the expansion process of the Child Education. Authors such as Áries, Enguita, Rousseau, Winnicott, among others, provided the basis for such study. Besides, it was tried to explore the curriculum concept, having an attentive eye to the theoretical proportions that its different approaches assumed towards Child Education and the documents which rule the proposal curriculum nation wide, the RCNEI and the Indicators of quality for the Child Education. Ivor Goodson, Gimeo Sacristán, Cesar Coll and Antonio Flavio Barbosa Moreira provided the basis for this study. Finally, they were analyzed the RCNEI and the Curricular Referential for the Child Education in Passo Fundo (RCEIPF) based on the quality indicators, aiming to discuss what is prescribed on the referential documents related to the curriculum for the Child Education, elaborated concerning federal and municipal levels. The analysis made clear that the Child Education universalization justifies itself, in the first place, because it is a social right of the child and that such process needs to ensure the possibilities of a full formation, which enables their emotional abilities, as well, social, motor, cognitive ones, and also that undertakes efforts towards their autonomy development. Therefore, it is necessary to have a curriculum which supports the Child Education professionals on the action and reflection they develop and that it may contribute for the production of a quality education in the infancy.